Analyzing the Determinants of Employee Performance in Public Healthcare: A Cross-Sectional Quantitative Study in a Community Health Center in Buleleng Regency - Dian Setiyawati; I Nengah Suarmanayasa; Made Ary Meitriana (International Journal of Management Science and Information Technology, 2026)
This study aims to empirically examine the influence of motivation, organizational culture, and job satisfaction on employee performance at the Gerokgak I Community Health Center, Buleleng Regency. The population consisted of all 59 employees, and a saturated sampling technique was applied, resulting in the entire population being used as the research sample. Data were collected through a structured questionnaire using a 5-point Likert scale. The data were analyzed using multiple linear regression with the assistance of IBM SPSS version 25. The results indicate that motivation (β = 0.525; p < 0.001), organizational culture (β = 0.263; p = 0.010), and job satisfaction (β = 0.244; p = 0.005) each have a positive and significant effect on employee performance. Among these variables, motivation emerged as the most influential factor, as indicated by the highest standardized coefficient. Simultaneously, the three independent variables significantly affect employee performance (F = 68.460; p < 0.001), with a coefficient of determination (R² = 0.789), indicating that 78.9% of the variance in employee performance can be explained by the model. These findings highlight the importance of strengthening employee motivation, supported by a conducive organizational culture and improved job satisfaction, to enhance performance in public healthcare institutions.